Gender differences in computer readiness among smart school teachers - Low, Siow Ngo (1999)
In order to help Malaysia make the critical leap into the Information Age, Smart Schools have been planned to help tum out students who are more technologically literate and who will become a thinking work force. Teachers of these Smart Schools must be computer-ready in order to help the education system undergo this radical transformation. As teachers play an important role in the implementation of the Smart School, their level of computer readiness will help them use computers and modem technology to support and enhance the teaching and learning process. The major purpose of this study was to determine gender differences in the level of computer readiness according to the components of computer readiness like attitude towards computer usage, current computer knowledge, interest in computer usage and computer usage. Questionnaires were sent out to teachers in Wilayah Persekutuan Kuala Lumpur who had undergone a 14-week in-service course and practicum to prepare them for teaching in Smart Schools. Data was obtained from 64 respondents in order to examine the level of computer readiness among teachers involved in the Smart School Project.